PELATIHAN KONDISI FISIK ATLET BULUTANGKIS BAGI KLUB PB. MAKASSAR RAYA - Muhammad Sadzali; Sarifin G; Hasmyati Hasmyati; Nur Indah Atifah Anwar; Benny Badaru (Program Studi Ilmu Keolahragaan, 2023)
Physical condition is one of the causes of badminton players at PB. Makassar Raya perform less well. Through briefings on the physical condition of badminton sports and how to improve it, coaches are given ways to help players maintain the physical condition of athletes which is very important for playing badminton. The goal is to be achieved so that the coach can understand the components of physical condition and how to improve it as part of an effort to achieve achievement. The output to be achieved from this service activity is that the coach has an understanding of the components of physical condition and how to improve it, as well as the publication of articles in scientific journals. The approach used to get there is 1) field observation and integration of partner participation, 2) Coach of PB. Makassar Raya will get a briefing on physical requirements, and 3) Evaluation of success in training activities.